Cardiovascular proteomics - Mary, Sheon; Schutte, Aletta E.; Currie, Gemma; Delles, Christian (Elsevier, 2020)
Cardiovascular diseases are the major cause of morbidity and mortality worldwide. They develop over long periods of time, and are typically caused by multiple factors, and interaction with the environment. Proteomics allows simultaneous quantification of multiple protein markers in a biosample, and therefore offers opportunities for precise individual definition of risk profiles, prediction, and diagnosis of disease. Proteomic biomarkers can also be used for monitoring of disease progression, and response to therapy. The large amount of information that can be obtained from comprehensive studies of the proteome naturally feeds into concepts of precision medicine, and has the potential not only to target preventative and therapeutic strategies to individual patients, but also to identify new therapeutic principles. In this chapter we will provide an overview of proteomic techniques, and how they can be applied in cardiovascular medicine
Keywords: Cardiovascular; Chronic kidney disease; Diabetes; Heart failure; Hypertension; Precision medicine; Proteomics